2012
DOI: 10.1007/s10517-012-1684-x
|View full text |Cite
|
Sign up to set email alerts
|

New Adamantane Derivatives Can Overcome Resistance of Influenza A(H1N1)pdm2009 and A(H3N2) Viruses to Remantadine

Abstract: New adamantane derivatives with amino acid residues and other bifunctional compounds were synthesized and their antiviral activity towards influenza A(H1N1)pdm and A(H3N2) viruses was studied. Some of these adamantane derivatives completely suppressed replication of remantadine-resistant influenza A virus strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…A method was proposed to overcome the resistance of influenza A viruses to adamantane series drugs by introducing new functional groups (carboxyl, hydroxyl, imidazole, indole, etc.) into the aminoadamantane carbocycle using amino acids, peptides, or other physiologically important compounds [ 28 ]. The resulting series of carbocyclic derivatives of amino acids and peptides is capable of inhibiting highly pathogenic strains of influenza A viruses, including A/H1N1pdm09, A/H5N1, A/H3N2, etc.…”
Section: Adamantane-type Derivatives With Anti-viral Activitymentioning
confidence: 99%
“…A method was proposed to overcome the resistance of influenza A viruses to adamantane series drugs by introducing new functional groups (carboxyl, hydroxyl, imidazole, indole, etc.) into the aminoadamantane carbocycle using amino acids, peptides, or other physiologically important compounds [ 28 ]. The resulting series of carbocyclic derivatives of amino acids and peptides is capable of inhibiting highly pathogenic strains of influenza A viruses, including A/H1N1pdm09, A/H5N1, A/H3N2, etc.…”
Section: Adamantane-type Derivatives With Anti-viral Activitymentioning
confidence: 99%
“…Аминокислоты обладают достаточно широким спектром боковых групп, которые могут привнести необходимые свойства будущей молекуле ингибитора. Более того, использование пептидов и некоторых других биологических молекул, введённых в адамантановый карбоцикл методами пептидного синтеза, может в значительной мере расширить поиск наиболее подходящего блокатора канала М2 вируса гриппа [7].…”
Section: оригинальные исследованияunclassified
“…Preclinical in vitro and in vivo studies demonstrated the pronounced activity of the new substance against rimantadine and amantadine resistant strains of influenza A virus in comparison with other analogs [12,13], which served as the basis for further clinical trials of H-His-Rim•2HCl•H2O. The identification of the new substance and the determination of its properties are crucial for further testing.…”
Section: Fig 1: Structural Formula Of L-histidyl-1-adamantylethylamin...mentioning
confidence: 99%